Anomalous branching pattern of common hepatic artery: a case report - Das, Sushant S.; Pangtey, Babita; Mishra, Sabita (International Journal of Research in Medical Sciences, 2017)
A number of hepatic artery variations exists which is continuously proving a hindrance for the surgeons and radiologists. During routine dissection in the subhepatic region in 50 year old male cadaver for undergraduate teaching, a variation in the branching pattern of common hepatic artery was noticed. We observed an unusual branching of the common hepatic artery into seven terminal branches, of which two were left hepatic arteries, two were right gastric arteries and the remaining three were right hepatic artery, cystic artery and gastroduodenal artery. Hepatic artery proper was absent. Embryological basis of these variations were discussed. The present case is a rarity and will further throw light on the knowledge of the hepatic artery variations, thus assisting surgeons and radiologists in various surgical and diagnostic procedures.